(untitled) (ModaPalavra e-periódico, 2021)
This essay aims to discuss the importance and repercussions of technological advance of the wearables in the quality of life. After the description of wearables applications and e-health development, we discuss how biotechnology, nanotechnology, internet of things, and artificial intelligence can affect freedom. Fashion, as the study of how people choose, can give important contributions to the development of proper quality of life. Fashion can help the discussions about how to balance the application of the wearables in daily life, individual freedom, and the welfare of the general public as well, the corporate interests.